2021
DOI: 10.3390/vaccines9101133
|View full text |Cite
|
Sign up to set email alerts
|

Oral Polio Vaccine Campaigns May Reduce the Risk of Death from Respiratory Infections

Abstract: Oral polio vaccine (OPV) campaigns, but not other campaigns, have been associated with major reductions in child mortality. Studies have shown that OPV reduces the risk of respiratory infections. We analysed the causes of death at 0–2 years of age in Chakaria, a health and demographic surveillance Systems in Bangladesh, in the period 2012–2019 where 13 national campaigns with combinations of OPV (n = 4), vitamin A supplementation (n = 9), measles vaccine (MV) (n = 2), and albendazole (n = 2) were implemented. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The majority of studies came from West Africa; however, studies from Bangladesh showed similar effects [ 32 , 34 , 41 ]. Most studies were natural experiments or RCTs, so adjustments for confounding factors are unlikely to remove the trends ( Supplementary Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies came from West Africa; however, studies from Bangladesh showed similar effects [ 32 , 34 , 41 ]. Most studies were natural experiments or RCTs, so adjustments for confounding factors are unlikely to remove the trends ( Supplementary Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two RCTs of OPV vs IPV in Bangladesh and Finland found that OPV reduced diarrhea and otitis media, respectively [ 9 ]. In Bangladesh, the mortality reduction associated with C-OPV was linked to prevention of fatal respiratory infections [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…It appears from our work that there is a correlation between breakthrough infections and cytokine levels after LAIV that is affected by concomitant vaccination. There is evidence of non-specific effects, including protection from respiratory disease, from other live vaccines in children 42 , 48 . This would suggest that some aspect of the immune response to the live vaccines is beneficial irrespective of the antigen content.…”
Section: Discussionmentioning
confidence: 99%
“…All five live attenuated vaccines have the strongest effect on respiratory infections, 5 , 6 , 20 , 59 , 60 , 61 and BCG has a strong effect on sepsis. 5 There has been little research into disease-differential effects of different live attenuated vaccines.…”
Section: Key Principles Of Non-specific Effects and Implications For ...mentioning
confidence: 99%